Minimum Inhibitory Concentration of Aloe Vera And Citrus Limon (L) Burm Extract. F As Antibacterial In Streptococcus Sp, Konsentrasi Hambat Minimum Aloe Vera Dan Citrus Limon (L) Burm Extract. F Sebagai Antibakteri Pada Streptococcus Sp - AFDILLA, NIA (Journal of Applied Health Management and Technology, 2022)
ABSTRACT            Aloe Vera and Citrus Limon are herbal plants that have various properties as antibacterial and antimicrobial. The active ingredients in aloe vera are anthraquinones, saponins, tannins, flavonoids, alkaloids and phenolics from phytochemical tests that act as antimicrobials and antibacterials. The substance that has many antibacterial properties in lemons is citric acid which is the main organic acid contained in lemon juice. Streptococcus sp is a bacterium commonly found after tooth extraction.                     This study aims to determine the effectiveness of aloe vera and citrus limon extracts as antibacterials with Minimum Inhibitory Concentration (MIC) against Streptococcus sp. Using Quasy Experiment pretest-posttest with control group design. Sampling was done by identifying tooth extraction tools exposed to Streptococcus sp media Nutrient Agar (NA). Bacterial testing using spectrophotometry is a fast way to count the number of bacteria in a solution using the liquid dilution method. Subjects were the concentration intervention group, namely 50%, 45%, 35%, 20%, 15%, 10%, 5%. This research uses a pharmaceutical chemistry laboratory and a microbiology laboratory. The results showed that the 5% concentration had effective bacterial inhibition against Streptococcus sp as evidenced by a large absorption value. The conclusion shows the combination of Aloe Vera and Citrus Limon extracts had a greater inhibitory power against Streptococcus sp.